(untitled) (Medicine Today, 2024)
Introduction: Chronic low back pain (LBP) is a major cause of abstinence from work in the world. Objective: The aim of the present study was to assess the epidemiological features of chronic low back pain patients in tertiary care teaching hospital. Materials and Methods: A descriptive cross sectional study was conducted from January 2018 to June 2018 among 70 patients attending at Physical Medicine and Rehabilitation outpatient department of the Shaheed Suhrawardy Medical College and Hospital after obtaining requisite consent from the patients. Data were collected through interviewing of the patients. The collected data were entered into the computer and analyzed by using SPSS (version 20.1) to assess the epidemiological features of chronic low back pain patients. Results: In a pool of 70 patients, most of the patients (n=34, 48.5%) belong to 31-40 year age group. In a pool of 70 patients, Male patients (52.85%) were more than the female patients (47.14%) at the Shaheed Suhrawardy Medical College and Hospital. In occupational status, most of the patients were Housewife (n=19, 27.14%) followed by service-holder (n=17, 24.28%). In a pool of 70 patients, most of the patients BMI were normal (n=49, 70%). Conclusion: Epidemiological features were characterized by male patients, as from the 31-40 years of life and housewife. Physical functional profile was primarily characterized by patients with normal BMI and overweight. Medicine Today 2024, Vol.36 (2): 107-109